NOTIONS OF SCHOOL BULLYING AND ITS APPROACH TO PREJUDICE: AN INTEGRATIVE REVIEW OF THE SCIENTIFIC LITERATURE - Letícia Leite Bessa (2023)
Introduction: School bullying is a social problem that has worried educators and researchers. Although there is a traditional notion about bullying, currently there are other understandings that expand or problematize the hegemonic view. Objective: to understand the meanings of bullying in Brazilian scientific research involving different areas of study, published in the last 5 years, observing similarities and differences within the prejudice theme. Method: qualitative research of exploratory nature, through an integrative review of the scientific literature. Articles available in SciELO and PubMed were searched using the descriptors Bullying AND Escola. Following inclusion and exclusion criteria, the research consisted of 21 articles in Portuguese. Results: The majority of studies are based on the traditional concept of bullying and only one problematizes this understanding. Regarding the approximation or distance between the concepts of bullying and prejudice, three positions appeared. In seven articles, approximations between the concepts of bullying and prejudice were not observed; in another seven, the relationship between the concepts appears indirectly, without problematizing this approximation; finally, in seven articles, this approximation is explicit and problematized. The last one discusses, for example, the greater exposure to the experience of bullying by black students, the LGBT+ community and women. The recurrence of these profiles as a target of bullying exposes the approximation of this type of violence to prejudice, intolerance and denial of diversity. Conclusions: The traditional meaning of bullying is present in research, however tensions were observed, such as studies that bring bullying closer to different expressions of prejudice. The studies qualitative approach contributes to a critical perspective that highlights bullying as a social and political problem and opens up to possibilities for other research questions and interventions in the context of school bullying in the path of social transformation.